Caries Patterns and Knowledge Levels About Prevention of Dental Caries in Elementary School Students: Pola Karies Dan Tingkat Pengetahuan Tentang Pencegahan Karies Gigi Pada Murid Sekolah Dasar St. Arnoldus Penfui Kupang - Yuliana N. R. Onlan; Ratih Variani; Apri A. Manu; Emma Krisyudhanti (Poltekkes Kemenkes Kupang, 2020)
In school children, dental caries is an important problem because it not only causes complaints of pain, but also causes infections to other parts of the body, resulting in decreased productivity. Knowledge of prevention of dental caries in children cannot be separated from the participation of health workers, nurses and doctors, to provide counseling and motivation to parents, the role of parents in the family environment. The survey results show that the elementary school students of St. Karolus Kupang class III and IV as many as 125 children who have dental caries so this study was conducted to determine the pattern of caries and the level of knowledge about prevention of dental caries in elementary school students St. Arnold Penfui Kupang. The type of research is descriptive and the research instrument is in the form of an examination and questionnaire format. The results showed that the pattern of dental caries in grade III-IV students of St. The most common Arnoldus penfui kupang was enamel caries with a total of 34% (46 teeth) and caries reaching the roots of 28% (39 teeth). Knowledge of prevention of dental caries is included in the moderate category of 41.8%. Based on the results of the study, it can be concluded that the pattern of dental caries in grade III and IV students of St. Arnoldus Penfui Kupang mostly had enamel caries and residual root caries and the level of knowledge about their prevention was moderate. It is recommended that children further improve dental health maintenance by reducing snacks that contain carbohydrates and for health workers to be more active in collaborating with the school. Pada anak sekolah, karies gigi merupakan masalah yang penting karena tidak saja menyebabkan keluhan rasa sakit, tetapi juga menyebabkan infeksi kebagian tubuh lainnya sehingga mengakibatkan menurunnya produktivitas. Pengetahuan pencegahan karies gigi anak tidak terlepas dari peran serta tenaga kesehatan perawat dan dokter untuk memberi penyuluhan dan motivasi pada orang tua, peran orang tua murid dalam lingkungan keluarga. Dari hasil survei menunjukkan murid sekolah dasar St. Karolus Kupang kelas III dan IV sebanyak 125 anak yang memiliki karies gigi sehingga penelitian ini dilakukan untuk mengetahui pola karies dan tingkat pengetahuan tentang pencegahan karies gigi pada murid sekolah dasar St. Arnoldus Penfui Kupang. Jenis penelitian deskriptif dan Instrumen penelitian berupa format pemeriksaan dan kuisoner. Hasil Penelitian menunjukkan bahwa pola karies gigi pada murid kelas III-IV sekolah dasar St. Arnoldus penfui kupang yang terbanyak adalah karies email dengan jumlah 34% (46 gigi) dan karies mencapai akar 28% (39 gigi). Pengetahuan pencegahan karies gigi termasuk dalam kategori sedang 41,8%. Berdasarkan hasil penelitian dapat disimpulkan bahwa pola karies gigi pada murid kelas III dan IV sekolah dasar St. Arnoldus Penfui Kupang yang terbanyak adalah karies email dan karies sisa akar dan tingkat pengetahuan tentang pencegahannya sedang. Disarankan agar anak – anak lebih meningkatkan pemeliharaan kesehatan gigi dengan mengurangi jajanan yang mangandung karbohidrat dan bagi tenaga kesehatan agar lebih aktif dalam bekerjasama dengan pihak sekolah.